Safety and tolerability of Meningococcus B vaccine in patients with chronical medical conditions (CMC) - L. Nicolosi; C. Rizzo; G. Castelli Gattinara; N. Mirante; E. Bellelli; C. Bianchini; V. Pansini; A. Villani (BMC, 2019)
Abstract Background Invasive meningococcal disease is a serious global health threat in the world; in 2016, the European Centre for Disease Control and Prevention reported 3280 confirmed cases (including 304 deaths) of Invasive Meningococcal Diseases in Europe. In Italy, in 2017 were reported 200 cases 41% of which due to menB serogroup. From January 2013 the European Medicines Agency (EMA) has authorized the marketing of the meningococcal B vaccine 4CMenB. Methods The study aimed to evaluate and complement the safety profile of 4CMenB in high risk children accessing the vaccine service of the Bambino Gesù Children's Hospital. All individuals aged six weeks or more receiving the meningococcal 4CMenB (Bexsero®) vaccine that approached the vaccine Centre at the Bambino Gesù Children's Hospital in Rome, were asked to participate. All parents or caregivers of vaccinated individuals in the study period, were recruited and requested to answer to a questionnaire on adverse events following immunization (AEFI) observed after 7 days, starting from the date of vaccination. Results During the study period (October 2016-October 2017), we collected 157 completed questionnaires (out of 200 distributed). Of those 132 were first doses and 25 were booster administered doses. The median age of the study population was 4.5 years (range 0.29 to 26.8 years), the majority of subjects were high-risk individuals (64%) with chronic health conditions. Overall, 311 adverse events were reported in the 7 days after vaccine administration. In particular 147 events (47%) after administration of first dose and 58 (19%) after the booster doses. A large majority of those events, were of little clinical importance and concentrated in the 24 h after vaccine administration. No hospitalizations or Emergency Department access were reported. Conclusions Results of our study demonstrated that the Bexsero® vaccine is almost well tolerated, with a low incidence of severe AEFIs. Our results also shown that the occurrence of AEFIs is similar within healthy and high risk children.